Zu einigen Legenden und Überlieferungen von Wasserquellen in BulgarienMyths and Legends About Water Sources in Bulgaria - Kolev, Nikolai (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this article the author analyses Bulgarian myths, legends and festive rites to illustrate the traditional beliefs and pagan notions about water, which lie at the core of many myths and legends about water sources, elves, dragons and water bulls as well as in Christian legends about gods and saints: Perun, Jesus, the Virgin Mary, St. George, St. Ivan Rilski, St. Naum, and others.